To solve the equation 9x + y = 22, you need to isolate one of the variables. You can do this by either substituting a value for one variable and solving for the other, or by rearranging the equation to solve for one variable in terms of the other. For example, if you choose to solve for y, you would subtract 9x from both sides to get y = 22 - 9x. If you choose to solve for x, you would subtract y from both sides to get 9x = 22 - y, then divide by 9 to solve for x.
44 = 9x +8 36=9x 4=x
9x+8=7x+22 To solve for x, combine like terms. (Subtract 7x from both sides, and subtract 8 from both sides. This will give you: 2x=14 Divide both sides by 2. The answer is x=7.
x=9
2x + 5x - 1 = 9x 7x - 1 = 9x -1 = 9x - 7x -1 = 2x -1/2=x
-2x2 + 9x - 12 = 0Then apply the quadratic formula.
44 = 9x +8 36=9x 4=x
9x+8=7x+22 To solve for x, combine like terms. (Subtract 7x from both sides, and subtract 8 from both sides. This will give you: 2x=14 Divide both sides by 2. The answer is x=7.
x=9
-9x + 4 = -50 -9x = -50 - 4 -9x = -54 -x = -6 x = 6.
2x + 5x - 1 = 9x 7x - 1 = 9x -1 = 9x - 7x -1 = 2x -1/2=x
-2x2 + 9x - 12 = 0Then apply the quadratic formula.
x - 10x = 9x, so 9x + 3 = 0, so 9x = -3 so x = -1/3
x + 8x = 477 9x = 477 x = 53
2x + 3 = 9x Subtract 2x from both sides: 3 = 7x Divide both sides by 7: 3/7 = x
2x+3=9x 3=9x-2x 3=7x x=3/7
9x = 60x = 60/9 = 6 2/3 (or 6.67)
2x + 9x simplified would be 11x